1993
DOI: 10.1115/1.2929308
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Aerodynamics and Gust Response in Compressors and Turbines

Abstract: A comprehensive series of experiments and analyses was performed on compressor and turbine blading to evaluate the ability of current, practical, engineering/analysis models to predict unsteady aerodynamic loading of modern gas turbine blading. This is part of an ongoing effort to improve methods for preventing blading failure. The experiments were conducted in low-speed research facilities capable of simulating the relevant aerodynamic features of turbomachinery. Unsteady loading on compressor and turbine bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 0 publications
4
32
0
Order By: Relevance
“…(The potential component was filtered out using the splitting theorem.) The first Fourier component, usually referred to as "gust" (Manwaring and Wisler, 1993), clearly shows the three-dimensionality of the NGV wake towards the root section. A very large velocity deficit occurs half a cycle or so earlier than that for the midheight wake.…”
Section: Sources Of Unsteadiness and Wave Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…(The potential component was filtered out using the splitting theorem.) The first Fourier component, usually referred to as "gust" (Manwaring and Wisler, 1993), clearly shows the three-dimensionality of the NGV wake towards the root section. A very large velocity deficit occurs half a cycle or so earlier than that for the midheight wake.…”
Section: Sources Of Unsteadiness and Wave Splittingmentioning
confidence: 99%
“…Such interactions are purely inviscid, hence the term potential interaction. Although it is possible to consider one bladerow only, either the stator or the rotor, with the unsteady pressure being specified as a boundary condition (Korakianitis, 1993;Manwaring and Wisler, 1993), it is probably better to perform a stage calculation (Giles, 1990b;Sayma et al, 1999), especially when the spacing between the bladerows is small, and when there are shock waves moving in the region between them.…”
Section: Introductionmentioning
confidence: 99%
“…A full stator}rotor interaction model using Navier}Stokes equations was developed in 2-D by Giles (1990b), and in 3-D by Rai (1987b). Results from some of the models above are compared with experimental data in the paper by Manwaring & Wisler (1992). A study of varying the blade numbers is reported by Korakianitis (1988 (1992), which presents an industrial forced response prediction system, also reviews much of the research in this area.…”
Section: Nature Of the Problemmentioning
confidence: 99%
“…Namely, the flow in the rotor frame is spatially periodic, repeating itself every rotor spacing. The axial wave number can then be determined from Equation 6. Thus the axial and tangential wave numbers for the nth harmonic are " S™ η -1.…”
Section: (6)mentioning
confidence: 99%